Microfluidic technologies for yeast replicative lifespan studies. (January 2017) - Chen, Kenneth L.; Crane, Matthew M.; Kaeberlein, Matt
Highlights: Several microfluidic platforms have been described for yeast aging studies. Microfluidics allows for more rapid analysis of yeast lifespan and age-associated phenotypes. Different yeast microfluidic systems have strengths and weaknesses, and none are yet optimal. There are barriers to wide use of yeast microfluidic systems that still need to be overcome. Abstract: The budding yeast Saccharomyces cerevisiae has been used as a model organism for the study of aging for over 50 years. In this time, the canonical aging experiment—replicative lifespan analysis by manual microdissection—has remained essentially unchanged. Recently, microfluidic technologies have been developed that may be able to substitute for this time- and labor-intensive procedure. These technologies also allow cell physiology to be observed throughout the entire lifetime. Here, we review these devices, novel observations they have made possible, and some of the current system limitations.